Household mobility and mortgage rate lock - Liebersohn, Jack; Rothstein, Jesse (Journal of Financial Economics, 2025)
Rising interest rates can create “mortgage rate lock” for homeowners with fixed rate mortgages, who can hold onto their low rates as long as they stay in their homes but would have to take on new mortgages with higher rates if they moved. We show mobility rates fell in 2022 and 2023 for homeowners with mortgages, as market rates rose. We observe both absolute declines and declines relative to homeowners without mortgages, who are unaffected by mortgage rate lock. Mobility declines are not explained by changes in home values. Overall, our estimates imply that rising interest rates reduced mobility in 2022 and 2023 for households with mortgages by 16% and caused $20bn of deadweight loss.